Kahoot! in a flipped classroom: A case study at Junior High School in Samarinda - Wiza Ananda; Abdul Halim (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2024)
The study explores the integration of Kahoot! within a flipped classroom approach at Junior High School in Samarinda, focusing on its impact on student involvement, motivation, and educational achievements in English language learning. The research employs a qualitative case study design involving first-grade students. Data collection methods include pre- and post-implementation surveys, semi-structured interviews, and observation. Thematic analysis analyzes the data, revealing insights into students’ experiences and perceptions. The study aims to contribute to both theoretical understanding and practical application of Kahoot! in language learning within a flipped classroom context. This study examines how Junior High School Samarinda uses Kahoot! in flipped classrooms, with an emphasis on how it affects student motivation, engagement, and academic performance when learning English. Data was gathered via surveys, interviews, and observations using a qualitative case study approach with students in first-grade students. The results showed that Kahoot! greatly raises student achievement and motivation, and average scores show a strong desire to use it. Although there are some technical difficulties and a learning curve, Kahoot! creates an engaging and dynamic learning environment that improves comprehension and retention of the content. The present study highlights the potential of Kahoot! to enhance academic results and suggests further investigation into creative pedagogical approaches that incorporate technology, like Kahoot!, to augment student involvement and the efficacy of instruction.